Severe damages caused by Malathion exposure in Colossoma macropomum - Silva de Souza, Samara; Machado, Rubia Neris; Custódio da Costa, Jaqueline; Campos, Derek Felipe; Sebrenski da Silva, Grazyelle; Fonseca de Almeida-Val, Vera Maria (Ecotoxicology and environmental safety, 2020)
The increase in pesticide use in response to agricultural demands poses a risk to non-target organisms, including fish. Integrated analysis of biochemical, histopathological and genetic parameters in fish exposed to Malathion insecticide provide information on the toxicity mechanisms of this pesticide, which is classified as a probable carcinogen for humans. The present study assessed the biological responses of Colossoma macropomum after exposure to Malathion. We started determining the lethal concentration, which is the concentration capable of killing 50% of the subjects in an acute toxicity test (LC50-96 h), which was 15.77 ± 3.30 mgL−1. The fish were, then, exposed to Malathion during 96 h at a sublethal concentration, 7.30 mgL−1. Overall, we observed an increased activity of biotransformation and antioxidant enzymes, which reduced production of mitochondrial reactive oxygen species after 96 h exposure, as well as kept constant the mitochondrial respiration, Acetylcholinesterase activity and DNA damage. However, fish exposed to insecticide presented severe gill histopathological damage and increased expression of proto-oncogene ras. Taken together, the results suggest that, after four days of exposure to the Malathion, C. macropomum efficiently activates its defense mechanisms, suggesting that the basal response mechanisms are responsive. On the other hand, histopathologic damages evidenced the adverse effects of Malathion on fish, since it promoted gill necrosis and increased the expression of ras oncogene that is directly related to tumorigenesis events. [Display omitted] •Malathion is an insecticide widely used in the Amazon, whose use does not follow technical recommendations.•Malathion exposure activates biotransformation and antioxidant mechanisms.•Malathion exposure reduces the production of mitochondrial ROS and causes gills histopathological damage.•There is no change in the tumour suppressor gene tp53 expression after Malathion exposure.•Malathion causes an increase in the expression of ras oncogene suggesting potential carcinogenic effects of this insecticide.